Pediatric nutrition in practice - Ahsan, Hanaa (World review of nutrition and dietetics / series editor Berthold Koletzko, 2022)
There is no other time in life when the provision of adequate and balanced nutrition is of greater importance than during infancy and childhood. During this dynamic phase of life, sufficient amounts and an appropriate composition of supplied substrates are of key importance for growth, functional outcomes, and the metabolic programming of long-term health and wellbeing. This condensed volume was compiled with the aim of providing concise information to readers who seek quick guidance on the practice of nutrition of infants, children, and adolescents. After the great success of the first two editions, the editors prepared this thoroughly revised and updated third edition with a truly international perspective to address challenges in both affluent and challenged populations around the world. This book of outstanding quality will be useful to many healthcare professionals around the world, and it will contribute to further enhancing the quality of feeding of healthy infants and children, as well as enhancing the standards of nutritional care in sick children.